1993
DOI: 10.1002/jor.1100110403
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin is an abundant protein in dissociative extracts of bovine fetal epiphyseal cartilage and nasal cartilage from newborns

Abstract: An abundant protein that is identical to the growth-associated protein pleiotrophin (PTN) has been isolated from dissociative extracts of bovine nasal and fetal epiphyseal cartilage. The yield from these tissues was at least 15 micrograms/g wet weight of cartilage. PTN was absent or was present only in trace amounts in mature articular cartilage. An analysis of tryptic fragments of PTN, held together with disulfide bonds, did not indicate any set pattern of cystine cross-links, which suggests a propensity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Differences in pleiotrophin expression exist between fetal cartilage with high levels and mature cartilage with low levels (Neame et al, 1993;Azizan et al, 2000). It would be of interest to assess the level of pleiotrophin expression in the rapidly growing antler to ascertain if there are differences as the antler grows and matures.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in pleiotrophin expression exist between fetal cartilage with high levels and mature cartilage with low levels (Neame et al, 1993;Azizan et al, 2000). It would be of interest to assess the level of pleiotrophin expression in the rapidly growing antler to ascertain if there are differences as the antler grows and matures.…”
Section: Discussionmentioning
confidence: 99%
“…HARP is also expressed in the uterus (3), cartilage (4), and bone extracts (5). Several reports have established a strong correlation between HARP expression and tumor growth and angiogenesis (6 -8).…”
mentioning
confidence: 99%
“…This polypeptide is a member of a new family of heparin-binding growth factors including the midkine (MK) (Kadomatsu et al 1988) and its chicken homologue, called retinoic acid-induced heparin binding (RI-HB) factor (Raulais et al 1991). Initially isolated from neonatal rat brain as a molecule that induced neurite outgrowth of embryonic neurons (Rauvala 1989), this polypeptide was also shown to be present in non-neuronal tissues, including heart (Hampton et al 1992), uterus (Milner et al 1989), cartilage (Neame et al 1993), and bone (Zhou et al 1992) extracts. In addition to its role during neuronal development, several studies have shown that HARP was able to induce the proliferation of epithelial, fibroblast, and endothelial cells (Li et al 1990;Courty et al 1991;Fang et al 1992) and to stimulate in vitro the characteristic processes of angiogenesis (Laaroubi et al 1994).…”
mentioning
confidence: 99%